2020
DOI: 10.1038/s41598-020-74078-w
|View full text |Cite
|
Sign up to set email alerts
|

Late first trimester circulating microparticle proteins predict the risk of preeclampsia < 35 weeks and suggest phenotypic differences among affected cases

Abstract: We hypothesize that first trimester circulating micro particle (CMP) proteins will define preeclampsia risk while identifying clusters of disease subtypes among cases. We performed a nested case–control analysis among women with and without preeclampsia. Cases diagnosed < 34 weeks’ gestation were matched to controls. Plasma CMPs were isolated via size exclusion chromatography and analyzed using global proteome profiling based on HRAM mass spectrometry. Logistic models then determined feature selection with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 87 publications
0
10
0
1
Order By: Relevance
“…PE is a multi-factorial, multisystemic pregnancy specific condition found typically after 20 weeks of gestation or early post-delivery (American College of Obstetricians and Gynecologists, 2019). Although clinical symptoms appear relatively late in pregnancy, PE pathology begins early, making the identification of potential biomarkers during the first trimester a possible strategy for identifying predictors of PE (McElrath et al, 2020). Several potential biomarkers already have been evaluated: C reactive protein (CRP), cytokines (IL-6, IL-8, TNF-α), microparticle proteins (C1RL, GP1BA, VTNC, and ZA2G), oxidative stress markers (malondialdehyde -MDA), and genetic factors (PAI-1 4G/5G polymorphism) (Black and Horowitz, 2018;Giannakou et al, 2018;Taravati and Tohidi, 2018;McElrath et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PE is a multi-factorial, multisystemic pregnancy specific condition found typically after 20 weeks of gestation or early post-delivery (American College of Obstetricians and Gynecologists, 2019). Although clinical symptoms appear relatively late in pregnancy, PE pathology begins early, making the identification of potential biomarkers during the first trimester a possible strategy for identifying predictors of PE (McElrath et al, 2020). Several potential biomarkers already have been evaluated: C reactive protein (CRP), cytokines (IL-6, IL-8, TNF-α), microparticle proteins (C1RL, GP1BA, VTNC, and ZA2G), oxidative stress markers (malondialdehyde -MDA), and genetic factors (PAI-1 4G/5G polymorphism) (Black and Horowitz, 2018;Giannakou et al, 2018;Taravati and Tohidi, 2018;McElrath et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular signatures of trophoblastic microparticles might also additionally offer crucial information about the condition of the placenta while non-placental microparticles, including exosomes, might also additionally mirror maternal health or disease state. In line with those findings, latest research identified potential biomarkers of preeclampsia with the examining the changes in the type, amount, and content material of these exosomes [79][80][81][82].…”
Section: Liquid Biopsy Of the Placentamentioning
confidence: 60%
“…For example, FCER2A (CD23) is associated with the activation of B cells ( 67 ). GP1BA , a glycoprotein component on the surface of platelets is often related to clotting function ( 68 ) and has also been considered to participate in lung inflammation ( 69 , 70 ). IL-7 is considered to activate eosinophils and has a pivotal function in allergic inflammation in asthma ( 71 ), but is also essential for T- and B-cell development ( 72 ).…”
Section: Discussionmentioning
confidence: 99%